Analysis of Pakistani Advertisements under Grice’s Cooperative Principles - Maryam, Fasiha; Mushtaq, Faiza; Sumaira (Pakistan Journal of Humanities and Social Sciences, 2023)
Language when used as a verbal medium carries variety of significant meanings. The cooperative principle is one of the major foundations for a comprehensive and smooth conversation. Language when used as a verbal medium carries variety of significant meanings. The cooperative principle is one of the major foundations for a comprehensive and smooth conversation. The research in hand aims to focus on the advertisements in relation to Grice’s Cooperative Principles. The thought-provoking observation is that advertisers target their audience by creating idealistic taglines which usually deviate from the cooperative principles of communication. Electronic media language can either form a conversational bond with the audience or can sway them in opposite. The data for the said purpose was collected through the advertisements being aired on Pakistani news channels and Pakistani drama channels at prime hour. The analysis covers the implications of maxims of the cooperative principles over the tag lines of these advertisements and the influential meanings that hid under their discourse. By using the analytical method and qualitative approach the researcher tried to emphasize the meanings of conversational implicatures with and without following the cooperative principles. These taglines are significant in capturing the mind of the population and so they are made attractive and memorable keeping this as a prime foundation. The implication of maxims resulted in understanding the influential meanings both apparent and hidden as well as led the researchers understand various ways of flouting of maxims that happens while creating the tagline ideas. Though maintaining the integrity to not to manipulate the audience rather convincing for a second thought.